Transition to the maternal role in women with addiction problems to psychoactive substances: conceptual map - Henriques, Carolina (2018)
The transition to motherhood is seen as a phenomenon where are interwoven multiple variables, where the experience of being a mother can be so significant andfull of pleasure, as associated with suffering and unhappiness processes.If we associate this phenomenon, itself multidimensional, the problem of adding the psychoactive substances, the spectrum of its complexity increases, whereas the mother experiences a set of changes associated with pregnancy, childbirth and postpartum, at the same time with their behaviourto addition to psychoactive substances. Looking for the integration of the concepts involved in the problems of transition to the maternal role in women with addition problems to psychoactive substances, we used the conceptual map as a basic tool for the organization of scientific knowledge in the field of study. We conclude from its analysis, that women with addition problems to psychoactive substances, in the process of transition to the maternal role, experience adjustment processes of adaptation and transition, where their past contexts, present and future perspectives converge maternal identity, as the individual characteristics of each woman (self-esteem, personal integrity and self-confidence).